Is Atypical Human Trypanosomosis an Emering Threat to Human Society? : A Debatable one Health Issue to Public Health Experts and Parasitologists - Rahul Parashar; LD Singla; Parmjit Kaur (International Journal of Veterinary Science and Research - Peertechz Publications, 2016)
Trypanosomosis is caused by different species of unicellular eukaryotic haemofl agellate Trypanosoma. Though human infection by animal species of trypanosomes is "not possible" as these species fails to infect humans due to innate immunity of the host due to presence of trypanolytic factor in human serum, however, across the world 20 patients with atypical human trypanosomosis are documented, eight of which are confi rmed between 1974 and 2014 due to improved molecular diagnostic assays. However, the numbers of cases are atypical human trypanosomosis caused by animal trypanosomes might be underestimated. Ten atypical cases of human trypanosomosis have so far been reported form Indian subcontinent. Out of these, nine cases were from India and one from Sri Lanka.Three cases of human T. evansi have been reported from the Indian subcontinent (one from Sri Lanka and two from India) during the last decade. Apart from these three cases, at least six more atypical human cases of trypanosomosis caused by rat trypanosome, T. lewisi have been reported. Two casualties due to non-tsetse transmitted trypanosomosis (NTTT) were also reported from India. High prevalence of these two animal trypanosomes in India is now a matter of concern for public health specialists. These raise it as an alarming situation of emerging new zoonotic disease and debatable one health issue to public health experts and parasitologist. There is a need to investigate disease with modern diagnostics by epidemiological based surveys in the fi eld to know the exact situation of the disease. Veterinarian can play very crucial role in diagnosis and control of disease, also by educate and re-educate people about the transmission, prevention and control of disease.